If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10h + 7s = 74 Solving 10h + 7s = 74 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-7s' to each side of the equation. 10h + 7s + -7s = 74 + -7s Combine like terms: 7s + -7s = 0 10h + 0 = 74 + -7s 10h = 74 + -7s Divide each side by '10'. h = 7.4 + -0.7s Simplifying h = 7.4 + -0.7s
| 2x+2=1x+5 | | 8(3n-3)=-24-3n | | 7x+6y=53 | | 6k-3=3k-12 | | 6-7x=7(1-3x)-1 | | 2(a+9)=23 | | 0=2c-5 | | 100xy-75x= | | 9e-1=10.7 | | 3p=39.6 | | 0=3-16t^2 | | x+74=93 | | 54+39= | | 108-4x=14x+16 | | 4x^-4y^5/x^3 | | h=3-16t^2 | | x+41=96 | | -151-1-x=7x+19 | | 2x^2+2x+(-1.5)=0 | | 6x-82=-90 | | 3(4z+1)-4(z-9)= | | -3x-7=-21 | | 86-6x=8x+21 | | 180-40= | | 18+22= | | 180-145= | | 90+26= | | (2-7i)(2-7i)= | | 112+42= | | 180-68= | | 39+29= | | 97+x=89 |